Analysis Of Several Variables that Affect The Production of Fertilizers in PT.Tiara Kurnia, Malang - Pojoh, Rachel Ribka (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to determine the variables that influence the production of organic fertilizer and to determine the most dominant variable affecting the production of organic fertilizer. This research is a quantitative research using time series data (2010-2014), which consists of 60 months obtained from PT.Tiara Kurnia. The analytical method used is the method of multiple linear regression analysis of the model modified Cobb-Douglas production function with software tools SPSS version 18.0 were used to determine the effect that occurs between the independent variables on the dependent variable.The results of this research explains that the variables inventories of raw material and consumer demand does not significantly influence the production of organic fertilizer, while the variables capital and the number of working hours significantly influence the same thing. Viewed from the use of several variables on the activities turned out to be the most dominant production is variable capital. Some suggestions which can be delivered based on research results is the company should make additional capital, control the quality of raw material, improving the quality of human resources / labor skills through training activities in order to meet its target of organic fertilizer production according to market demand and government support is needed to improve organic fertilizer production in PT.Tiara Kurnia, Malang. Keywords: Organic fertilizers production, capital, number of working hours, inventories of raw material, consumer demand.